Pharmaceutical cost-sharing systems and savings for health care systems from parallel trade - Laura Birg (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2013)
This paper analyzes the consequences of parallel trade on health care systems in a two-country model with a vertical distributor relationship. In particular, two cost-sharing systems - coinsurance and indemnity insurance - are compared with respect to changes in copayments and public health expenditure. Under both cost-sharing systems, parallel trade generates a price-decreasing competition effect in the destination country and a price-increasing double marginalization effect in the source country. In the destination country, copayments for patients decrease to a larger extent under indemnity insurance, whereas reductions of public health expenditure occur only under coinsurance. In the source country, copayments increase less under coinsurance, whereas health expenditure is reduced more under indemnity insurance. This illustrates that a harmonization of health care systems would not make sense.
Keywords: F12; I11; I18; 330; cost-sharing; parallel trade; coinsurance rates; indemnity insurance